2011
DOI: 10.1002/zoo.20390
|View full text |Cite
|
Sign up to set email alerts
|

Semen Characteristics and artificial insemination in rockhopper penguins (Eudyptes chrysocome chrysocome)

Abstract: This work was performed as part of a multi-year study to determine the cause of the low fertility in captive rockhopper penguins (Eudyptes chrysocome chrysocome) and attempt to increase the fertility through artificial insemination (AI). Semen collection and characterization was performed on 14 male rockhopper penguins. The samples were evaluated for volume, sperm concentration, and sperm quality (motility, forward motility, viability, and morphology). There was a large variation between individuals and betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The fact that the majority of morphological abnormalities (50.2%) are located in the head region corresponds to findings in other avian species, such as passerines [Lüpold et al, 2009], emus [du Plessis andSoley, 2011], penguins [Waldoch et al, 2012], and psittacines [Stelzer et al, 2005[Stelzer et al, , 2009. The mean rate of 26.5% (range 6.0-55.0%) morphologically normal spermatozoa was low compared to 42-65% normal spermatozoa in three conure species (Aratinga acuticaudata, A. solsttialis, Guarouba guarouba) and 95% in blue-napped parrots [Stelzer et al, 2005].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The fact that the majority of morphological abnormalities (50.2%) are located in the head region corresponds to findings in other avian species, such as passerines [Lüpold et al, 2009], emus [du Plessis andSoley, 2011], penguins [Waldoch et al, 2012], and psittacines [Stelzer et al, 2005[Stelzer et al, , 2009. The mean rate of 26.5% (range 6.0-55.0%) morphologically normal spermatozoa was low compared to 42-65% normal spermatozoa in three conure species (Aratinga acuticaudata, A. solsttialis, Guarouba guarouba) and 95% in blue-napped parrots [Stelzer et al, 2005].…”
Section: Discussionsupporting
confidence: 81%
“…Some of these problems might be solved by assisted reproduction [Blanco et al, ]. Semen donors might be evaluated and selected according to results of semen analysis offering better breeding options [Neumann et al, ]; semen collection and artificial insemination (AI) have been used in domestic fowl [Burrows and Quinn, ] and in falconry [Temple, ] for decades and have been described as useful tools in the conservation of rare avian species [Blanco et al, ; DOC, ; Waldoch et al, ]. In psittacines, semen collection via massage method and semen analysis have been performed in smaller species [Samour et al, ; Anderson et al, ; Samour, ; Stelzer et al, , ; Neumann et al, ], but rarely reported in larger parrots [Brock, ; DellaVolpe et al, ], and with only moderate success rates.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal traits based on the two males in this study revealed that king penguins produce ejaculates of high quantity and quality compared with the two other penguin species where ejaculate characterization has been reported (Magellanic: O'Brien et al, ; rockhopper: Waldoch et al, , ). Specifically, the total sperm number per ejaculate for the king penguin (563.4 × 10 6 ) was 49‐ and 86‐fold higher than that of the Magellanic (11.4 × 10 6 ) and rockhopper (6.57 × 10 6 ) penguin, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…Research on basic reproductive biology and sperm preservation is needed for each penguin species to enhance natural reproduction and successfully apply AI. Seminal traits have been reported for the Magellanic penguin ( Spheniscus magellanicus ) using semen from one male (O'Brien et al, ) and for the rockhopper penguin ( Eudyptes chrysocome chrysocome ; Waldoch et al, , ). Semen preservation has been reported in the former species (O'Brien et al, ), but similar information for the king penguin is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Samtools v0.1.19 with the command mpileup and Bcftools v0.1.19+ were used to perform single-nucleotide variant calling ( Ramirez-Gonzalez et al, 2012 ; Etherington et al, 2015 ; Danecek et al, 2021 ). Rockhopper (2.0.3) was employed to predict operons, transcription start sites, and transcription stop sites ( Waldoch et al, 2012 ). RBSfinder (v1.0) was used for Shine–Dalgarno sequence prediction ( Florensa et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%